The Impact Of Brand Ambassadors And Lifestyle On Purchase Decision: Mediating Role Of Brand Image (Case Study of Consumers Using Somethinc Products in Yogyakarta City) - Wahyu Saputri, Febriani; Welsa, Henny (International Conference on Humanity Education and Society (ICHES), 2024)
Purchasing decisions are the action of choosing from various alternatives (two or more options) to determine a decision to purchase a product/service. In this way, an individual can arrange various choices according to their needs and desires. Some articles have been proven to have a positive and significant influence, but other research has not been proven to have a positive and significant influence on purchasing decisions. This research is needed to further explore what variables have an influence on increasing purchasing decisions and adding brand image as a mediator. This research aims to determine the influence of brand ambassadors and lifestyle on purchasing decisions for certain products through brand image as a partial and simultaneous intervening variable. This research method involved 105 consumer respondents using Somethinc products with a sampling technique using non-propability with purposive sampling, while data processing used the IMB SPSS 25 application. The results showed that brand ambassadors and lifestyle had a positive and significant effect on brand image. Brand ambassadors and lifestyle have a positive and significant influence on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Apart from that, mediation analysis shows that brand image is able to mediate brand ambassadorship and lifestyle on purchasing decisions.